2023
DOI: 10.1021/acsphyschemau.3c00009
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Dynamics of Gas-Phase Bimolecular Reactions with Submerged Barriers

Abstract: Much attention has been paid to the dynamics of both activated gas-phase bimolecular reactions, which feature monotonically increasing integral cross sections and Arrhenius kinetics, and their barrierless capture counterparts, which manifest monotonically decreasing integral cross sections and negative temperature dependence of the rate coefficients. In this Perspective, we focus on the dynamics of gas-phase bimolecular reactions with submerged barriers, which often involve radicals or ions and are prevalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 155 publications
(345 reference statements)
1
6
0
Order By: Relevance
“…We note in passing that mode specificity is typically absent for barrierless complex-formation reactions, as the long-lived intermediate typically results in LOM . However, for some reactions with a submerged barrier, mode specificity might survive, as the submerged barrier serves as a reaction bottleneck …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We note in passing that mode specificity is typically absent for barrierless complex-formation reactions, as the long-lived intermediate typically results in LOM . However, for some reactions with a submerged barrier, mode specificity might survive, as the submerged barrier serves as a reaction bottleneck …”
Section: Discussionmentioning
confidence: 91%
“…52 However, for some reactions with a submerged barrier, mode specificity might survive, as the submerged barrier serves as a reaction bottleneck. 53 As an interesting note, only the excitation of a vibrationally pure state is considered in this work. Care should be exercised for the vibration of the superposition-state nature or the eigenstate that comprises several zero-order states with nonnegligible mixing coefficients, which are ubiquitous for highervibrationally excited states or in larger molecules.…”
Section: The Journal Ofmentioning
confidence: 99%
“…Most gas-phase ion–molecule reactions are dominated by long-range electrostatic forces between the charge of the ion and the multipole moments of the molecule, allowing the two reactants to be captured by a deep potential well that supports a reaction intermediate. Therefore, rate coefficients of such reactions predicted with the aid of capture theories work well. , The transition state (saddle point in potential energy surface) between the reaction intermediate and the product along the reaction coordinates is also common for ion–molecule reactions. If the transition state is submerged with regard to the entrance channel, it will act as a bottleneck in the reaction rather than altering the capture characteristic . These features underscore that the possibility of the coexistence and competition between different microscopic reaction mechanisms, while nonstatistical dynamics, such as nonintrinsic reaction coordinate (IRC) dynamics, are often important. The reaction between a silicon cation and a water molecule is a typical ion–molecule reaction with submerged barriers.…”
Section: Introductionmentioning
confidence: 98%
“…3−5 If the transition state is submerged with regard to the entrance channel, it will act as a bottleneck in the reaction rather than altering the capture characteristic. 6 These features underscore that the possibility of the coexistence and competition between different microscopic reaction mechanisms, while nonstatistical dynamics, such as nonintrinsic reaction coordinate (IRC) dynamics, are often important. 7−10 The reaction between a silicon cation and a water molecule is a typical ion−molecule reaction with submerged barriers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Recently, it has, however, been found that the submerged barrier, straddling the pre-and post-saddle point (SP) wells in a number of ion-molecule reactions, exerts some control on the reactivity, resulting in non-statistical behavior. 9,13,[22][23][24] The gas-phase ion-molecule reaction between beryllium hydride ion (BeH + ) and water molecules (H 2 O) has attracted some attention in recent years due to its possible role in qubit loss. [25][26][27] Metal ions such as Be + , Mg + , Ca + , Sr + , Ba + , and Yb + were used to carry quantum bits for quantum information processing.…”
Section: Introductionmentioning
confidence: 99%